A study of hydatidosis by means of computed tomography - Wozniak, Angélica; Luongo, Alvaro; Pou, Gonzalo (Cirugía del Uruguay, 1981)
This paper is based on 35 hydatid cyst cases, diagnosed and corroborated by surgery, which were studied over an llfcmonth period in the Computed Tomography Centre of Larghero Hospital.